Investigate the Presence of Balantidium coli in Human Feces and House Rats in Several Regions of AL-Ramadi City (Journal of Pharmaceutical Negative Results, 2022)
The isolated fecal samples were taken from 113 individuals suffering from abdominal pain and colic and watery diarrhea with blood and mucosa. The patients ranged in age from (1-12) years from various districts in Al-Anbar province to the Al-Ramadi hospital. After detecting Balantidium coli inside the fecal samples, were taken (279) fecal samples from house rodents in the same research regions were immediately brought to the laboratory and evaluated using the Floatation technique with NaCl solution to generate wet mounts for Balantidium coli and stained with Logal's iodine. The immediate results showed a percentage of (45.1%) in girls and (54.8%) in males of all infected cases. The infection rate in ages 1-3 years was higher (38.9%), While the rate in ages 10–12 years (7.9%). The overall number of infected cases within all study locations was observed as a percentage (12.3%), with Al-Jazeera Q having the highest number, followed by AL-Sofia Q. The feces recovered from these rodents included a significant percentage of isolated trophozoite and cyst-stage Balantidium coli infections, 88(19.5) of the total collected samples (279). Al-Jazeera had the largest percentage of infected individuals, followed by Al-Sofia, while Al-Tamim Q had the lowest percentage.  Finally, balantidiasis is uncommon throughout Iraq for the absence of pigs. As a result, this study discovered that Balantidium coli infections in Al-Ramadi city were a result of the high level of environmental pollution as well as the degradation of health care owing to the political situation in recent years. percentage of (5.71%).